Pentacene homojunctions: Electron and hole transport properties and related photovoltaic responses - Harada, K; Riede, M; Leo, K; Hild, O; Elliott, C (American Physical Society, 2008)
We report on organic p-i-n homojunctions composed of differently doped vacuum-deposited pentacene layers. We observe a remarkably high built-in voltage of 1.65 V. An analysis of the current-voltage characteristics under dark and illuminated conditions reveals that the open-circuit voltage is directly related to the built-in voltage and that the recombination process is influenced by the distinct charge transport properties of electrons and holes in the pentacene film. By a comparison with p-i-p and n-i-n single-carrier homojunctions, deep trap states located around 0.63 eV below the electron transport level are shown to influence the properties. © 2008 The American Physical Society.